PVA, PVA blends, and their nanocomposites for biodegradable packaging application - Abdullah, Zainab; Dong, Yu; Davies, Ian; Barbhuiya, Salim (Taylor & Francis, 2017)
This review exclusively addresses material systems primarily based on poly(vinyl alcohol) (PVA), one of the most popular water-soluble biopolymers, for their use in packaging applications with the primary objective of reducing petrobased plastic waste. In addition, some typical PVA blends and nanocomposites are discussed as comparative studies for material packaging. Structural characteristics, mechanical, thermal, and barrier properties, in addition to biodegradation of these multiple material systems are summarized in a systematic manner. Finally, associated fabrication processing methods together with the most popular theoretical models used for the permeability of PVA nanocomposites are also reviewed in detail.